Digital Health Insurance System in Bangladesh: Facilitating Health Expenditure and Ensuring Health Security - Md. Shafiul Alam Bhuiyan; Md. Ziaur Rahman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The implementation of digital health insurance systems represents a pivotal shift in healthcare management globally, aiming to streamline processes, enhance accessibility, and mitigate financial barriers to healthcare services. This study investigates the impact of digital health insurance on health expenditure and health security in Bangladesh, a country striving to improve its healthcare infrastructure and financial accessibility. However, in Bangladesh health insurance does not exist and people has to bear all treatment cost alone. The insurer in development countries is changing its role toward a more preventive and connected approach. Connected or digital health insurance has the potential to contribute toward better health and the general well-being of the population. Digital technologies are evolving and innovative applications are transforming the medical and health insurance sector. New technologies like wearable, mobile platforms and IoT base health monitoring systems can help to deal with several critical issues of the rising number of people, patients with chronic disease, and aging people, the insurer can help them to be healthier and protect them by insurance coverage. This study aims to look at the innovation of Health insurers and how they include themselves in the health ecosystem that adds value for the insured and patients globally, and can proposed a model that can introduce in Bangladesh.